KMT2 (MLL) family of methyltransferases in head and neck squamous cell carcinoma : a systematic review - Santos, Marcos Ezequiel da Silva (2023)
Background: The involvement of the KMT2 methyltransferase family in the pathogenesis of head and neck squamous cell carcinoma (HNSCC) remains elusive. Method: This study adhered to the PRISMA guidelines, employing a search strategy in the LIVIVO, PubMed, Scopus, Embase, Web of Science, and Google Scholar databases. The methodological quality of the studies was assessed by the Joanna Briggs Institute. Results: A total of 33 studies involving 4294 individuals with HNSCC were included in this review. The most important alteration was the high mutational frequency in the KMT2C and KMT2D genes, with reported cooccurrence. The expression of the KMT2D gene exhibited considerable heterogeneity across the studies, while limited data was available for the remaining genes. Conclusions: KMT2C and KMT2D genes seem to have tumor suppressor activities, with involvement of cell cycle inhibitors, regulating different pathways that can lead to tumor progression, disease aggressiveness, and DNA damage accumulation.